MANAJEMEN TALENTA BERBASIS TEKNOLOGI INFORMASI DI SEKOLAH MENENGAH ATAS SWASTA HANG TUAH 4 SURABAYA - Silvia Putri Ardilla; Syunu Trihantoyo; Ainur Rifqi; Erny Roesminingsih (STKIP Pesisir Selatan, 2025)
This study aims to analyze the implementation of information technology–based talent management in supporting the effectiveness of human resource management at SMAS Hang Tuah 4 Surabaya. The research is motivated by the digital era’s demand for teachers to possess not only pedagogical competence but also strong digital literacy. A descriptive qualitative approach was employed, utilizing interviews, observations, and documentation as data collection techniques. The findings reveal that the use of digital applications such as Sulinjar, Afresto, Cooding AI, and Artikuret Story Telling has enhanced teacher professionalism, fostered collaboration, and built an innovation-oriented work culture. Talent planning was conducted using data-driven analysis to design appropriate development programs, while talent assessment was carried out through direct classroom supervision to ensure authentic performance evaluation. The study highlights that the success of this digital transformation depends on visionary leadership, institutional support, and adequate digital infrastructure. Despite challenges related to teachers’ varying levels of digital literacy, the research concludes that integrating information technology into talent management effectively improves efficiency, transparency, and the quality of educational human resources toward an adaptive and sustainable management system.